PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. WINSTAR LOGISTIK BATAM - Brigida Endah Nuraeni; Laurensius Dihe Sanga; Indra Firdiyansyah (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
The study aims to know how compensation, motivation and work environment affect Batam’s PT. Sekupang Logistics workers’ performance. The method used for taking sampels in this study is the census method, the sample used in this study 30 respondents in the entire PT. Sekupang logistics of Batam. Data cellection is done with a questionnaire’s technique. Whereas the analysis of data uses quantitative data analysis that is validity, reliability testing, the classic assumption of multiple linier regresion analysis, coefficiencies (R2) and hypothetical testing through t (partial) and f (simultaneous). The result of this study was the multiple linier regression equation Y= 27,54 -0,077 -0,108 + 0,079. The value of R square is 0,048, means to show that compensation variables (X1), motivation (X2) and work environment (X3) can only employees performance variables of 4,8%, while 95,2% are explained by other variables not discussed in the study